Sulfur speciation in a tropical soil under long-term no-till amended with lime and phosphogypsum - Costa, Rodolfo Fagundes (2020)
Sulfur (S) is a plant nutrient usually required in great amounts by yielding crops. Plants absorb S mainly as inorganic sulfate (SO42-), but this element is presented greatly in organic forms (> 90 %) in the most superficial layers of well-drained soils. The conversion of organic S forms to (SO42-) is mediated by microrganisms and is an important source of S for plants, especially in natural systems or agricultural systems that received little or no S input. A decrease in S content in soil is related to the depletion of soil organic matter (SOM) after converting natural forest to agriculture fields, and the adoption of no-tillage (NT) system is an alternative to increase it. Lime is applied to highly wheathered tropical soils to increase pH and serve as a source of Ca and Mg. On the other hand, phosphogypsum acts as a source of Ca and S in depth and decrease Al tocixity in depper leayers. In this study, the effects of these greater recommendation rates of phosphogypsum, in association or not with lime, were evaluated on S dynamics, soil chemical attributes and enzyme activity of a soil under NT as compared to anative forest soil. Synchrotron-based X-ray absorption near-edge structure spectroscopy (XANES) was used as noninvasive tool to direct determination of S forms in soils after a linear combination fitting (LCF) analysis on S K-edge XANES spectra of soil samples. The following attributes were evaluated: soil pH, contentes of SOM, sulfate, exchangeable cations (K, Ca and Mg) and soil enzymes (β-glucosidase and arylsulfatase) activity. SOM was affected by land use change andamendments\' application. Phosphogypsum application increased contents of inorganic sulfur in depper layers and changed the distribution of organic and inorganic S fractions. LCF analyses were a good indicator of S fractions, but did not match the proportion of organic and inorganic S fractions to the wet-chemical analysis. Lime increased soil pH until 40 cm depth and also decreased exchangeable Al3+ when compared to phosphogypsum and native forest soil. Phosphogypsum decreased exchangeable K contents in surface, when compared to control and native forest soil. The combination of amendments promoted a great translocation of Ca applied to the surface to depper depths. Exchangeable Mg content decreased when only phosphogypsum was applied. β-glucosidase activity decreased with depth for all treatments and native forest soil and increased with lime and phosphogypsum application. Arylsulfatase activity increased in treatments that received lime and deacresed with application of phosphogypsum alone when compared to control and were similar to native forest soil down to 20 cm depth.